2020
DOI: 10.1038/s41586-020-1991-8
|View full text |Cite
|
Sign up to set email alerts
|

Preindustrial 14CH4 indicates greater anthropogenic fossil CH4 emissions

Abstract: Atmospheric methane (CH 4) is a potent greenhouse gas, and its mole fraction has more than doubled since the preindustrial era 1. Fossil fuel extraction and use are among the largest anthropogenic sources of CH 4 emissions, but the precise magnitude of these contributions is a subject of debate 2,3. Carbon-14 in CH 4 (14 CH 4) can be used to distinguish between fossil (14 C-free) CH 4 emissions and contemporaneous biogenic sources; however, poorly constrained direct 14 CH 4 emissions from nuclear reactors have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
179
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 232 publications
(216 citation statements)
references
References 30 publications
(55 reference statements)
6
179
0
2
Order By: Relevance
“…The main bottom-up global inventory datasets covering anthropogenic emissions from all sectors (Table 1) are from the United States Environmental Protection Agency (USEPA, 2012), the Greenhouse gas and Air pollutant Interactions and Synergies (GAINS) model developed by the International Institute for Applied Systems Analysis (IIASA) (Gomez Sanabria et al, 2018;, and the Emissions Database for Global Atmospheric Research (EDGARv3.2.2; Janssens-Maenhout et al, 2019) compiled by the European Commission Joint Research Centre (EC-JRC) and Netherland's Environmental Assessment Agency (PBL). We also used the Community Emissions Data System for historical emissions (CEDS) (Hoesly et al, 2018) developed for climate modelling and the Food and Agriculture Organization (FAO) dataset emission database (Tubiello, 2019), which only covers emissions from agriculture and land use (including peatland and biomass fires).…”
Section: Global Inventories Gatheredmentioning
confidence: 99%
“…The main bottom-up global inventory datasets covering anthropogenic emissions from all sectors (Table 1) are from the United States Environmental Protection Agency (USEPA, 2012), the Greenhouse gas and Air pollutant Interactions and Synergies (GAINS) model developed by the International Institute for Applied Systems Analysis (IIASA) (Gomez Sanabria et al, 2018;, and the Emissions Database for Global Atmospheric Research (EDGARv3.2.2; Janssens-Maenhout et al, 2019) compiled by the European Commission Joint Research Centre (EC-JRC) and Netherland's Environmental Assessment Agency (PBL). We also used the Community Emissions Data System for historical emissions (CEDS) (Hoesly et al, 2018) developed for climate modelling and the Food and Agriculture Organization (FAO) dataset emission database (Tubiello, 2019), which only covers emissions from agriculture and land use (including peatland and biomass fires).…”
Section: Global Inventories Gatheredmentioning
confidence: 99%
“…The isotope 14 C is rather steadily produced by the interaction of cosmic radiation with atmospheric nitrogen. As 14 C decays with a half-life of~5730 years [34] and dead organic materials stop incorporating 14 C, the 14 C concentration is used for so-called radiocarbon dating but can be also used to differentiate among methane sources [35]: 14 C has completely decayed in fossil (thermogenic) methane, whereas biogenic and pyrogenic methane sources typically processing recent carbon sources have 14 C levels similar to the atmospheric CO 2 [36]. (CH 4 ) showing a possibility to categorize methane emissions according to the emission pathway.…”
Section: Differences Between Anthropogenic and Natural Methane Emissionsmentioning
confidence: 99%
“…Further progress to reduce the uncertainty has been made with radioactive isotopic methane measurements. Hmiel et al [35] measured 14 C levels of 11,660-year-old atmospheric methane in an ice core. They found that natural CH 4 emissions from geologic ( 14 C-free) sources were highly overestimated in the literature and that current models therefore underestimated the amount of current anthropogenic methane emissions from fossil fuels by 33% over the upper uncertainty threshold [13,35].…”
Section: Reducing the Uncertainty Of Global Emission Inventoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of urban CH 4 emissions in California indicate that the California Air Resources Board (CARB) inventory tends to underestimate the actual CH 4 urban fluxes, possibly due to fugitive emissions from NG infrastructures in urban environments (Wunch et al, 2009;Jeong et al, 2016Jeong et al, , 2017. The accuracy and precision of atmospheric estimates of urban CH 4 emissions are limited by available atmospheric observations (Townsend-Small et al, 2012), potential source magnitude variability with time (Jackson et al, 2014;Lamb et al, 2016), errors in atmospheric transport modeling (Hendrick et al, 2016;Deng et al, 2017;Sarmiento et al, 2017), and complexity in atmospheric background conditions (Cambaliza et al, 2014;Karion et al, 2015;Heimburger et al, 2017). In this work, detailed analysis of urban CH 4 mole fractions is performed for the city of Indianapolis to better understand the aforementioned uncertainties of urban CH 4 emissions.…”
Section: Introductionmentioning
confidence: 99%